2021
DOI: 10.1155/2021/6740696
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Optimization of Damping Properties of Constrained Layer Damping Structures with Multilayers

Abstract: Constrained layer damping (CLD) structures, which are one of the composite structures with a softer viscoelastic material (VEM) layer sandwiched between a elastic base layer and a relatively stiffer constraining layer, are widely used in engineering applications for reducing vibration and noise radiation. To accurately predict and effectively control vibration and properly and quickly determine the design parameters, optimal designs for the CLD structures are necessary. The optimal designs depend on thoroughly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…[20][21][22][23] Reports on their analysis at the system level (CLD or FLD) representing the real-time scenario of their application is rather scanty. [24][25][26] Prediction of vibration damping can be carried out using either closed-form solutions or the finite element method (FEM) with the aid of commercial software for numerical analysis. 9,[27][28][29] FEM has emerged as a robust tool for numerical modal analysis and harmonic analysis of vibrating substrates and systems integrating CLD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23] Reports on their analysis at the system level (CLD or FLD) representing the real-time scenario of their application is rather scanty. [24][25][26] Prediction of vibration damping can be carried out using either closed-form solutions or the finite element method (FEM) with the aid of commercial software for numerical analysis. 9,[27][28][29] FEM has emerged as a robust tool for numerical modal analysis and harmonic analysis of vibrating substrates and systems integrating CLD.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the studies on VEMs reported in the literature pertain to their evaluation of loss factors from DMA 20–23 . Reports on their analysis at the system level (CLD or FLD) representing the real‐time scenario of their application is rather scanty 24–26 . Prediction of vibration damping can be carried out using either closed‐form solutions or the finite element method (FEM) with the aid of commercial software for numerical analysis 9,27–29 .…”
Section: Introductionmentioning
confidence: 99%
“…When the modulus of the constraint layer is small, the composite loss factor of the constrained damping structure decreases slightly as the number of layers increases. Wang et al 18 studied the influence of constraint layer thickness on the damping characteristics of constrained damping structures using finite element method. They found that increasing the thickness of constraint layer actually increases the constraint shear force, thereby improving the damping performance of constrained damping structures.…”
Section: Introductionmentioning
confidence: 99%